Discourse analysis: what is it and why is it relevant to family practice? - E Shaw, S; Bailey, J (Oxford University Press, 2009)
This paper aims to illustrate what discourse analysis is and how it can contribute to our understanding of family practice. Firstly, we describe what ‘discourse analysis’ is, mapping the discourse analysis terrain by discussing four studies relevant to primary care to illustrate different methodological approaches and key concepts. We then address the practicalities of how to actually do discourse analysis, providing readers with a worked example using one particular approach. Thirdly, we touch on some common debates about discursive research. We conclude by advocating that researchers and practitioners take up the challenge of understanding, utilizing and extending the field of discourse studies within family practice.